2020
DOI: 10.3390/v12070711
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Persistence and Chronic Induction of Innate Immune Responses in Macrophages

Abstract: A hallmark of HIV-1 infection is chronic inflammation, which plays a significant role in disease pathogenesis. Acute HIV infection induces robust inflammatory responses, which are insufficient to prevent or eliminate virus in mucosal tissues. While establishment of viral set-point is coincident with downregulation of acute innate responses, systemic inflammatory responses persist during the course of chronic HIV infection. Since the introduction of combination antiviral therapy (cART), most HIV-1+ individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 163 publications
(222 reference statements)
1
14
0
2
Order By: Relevance
“…At 48 h post-treatment, the fluorescence intensity began to diminish, but we still observed a high quantity of G2-S16 dendrimer inside the cells. As reported in the scientific literature, viral particles are able to resist inside macrophages, maintaining the ability to infect new T lymphocytes [24][25][26]. In our results, we observed at 72 h post-treatment that fluorescence intensity decays to low levels but is still observable using confocal microscopy.…”
Section: G2-s16 Dendrimer Internalizes Into Monocyte-derived Macrophages and Is Stable For 48 Hsupporting
confidence: 82%
“…At 48 h post-treatment, the fluorescence intensity began to diminish, but we still observed a high quantity of G2-S16 dendrimer inside the cells. As reported in the scientific literature, viral particles are able to resist inside macrophages, maintaining the ability to infect new T lymphocytes [24][25][26]. In our results, we observed at 72 h post-treatment that fluorescence intensity decays to low levels but is still observable using confocal microscopy.…”
Section: G2-s16 Dendrimer Internalizes Into Monocyte-derived Macrophages and Is Stable For 48 Hsupporting
confidence: 82%
“…Thus, overall, our data are consistent with some of the earlier reports showing that incoming HIV-1 particles are not a strong inducer for a type I IFN response that depends on cGAS sensing of HIV-1 DNA ( 11 , 31 , 42 , 47 , 60 , 84 86 ). It should be noted, however, that the early phase is not the only period during which HIV-1 can be sensed, as multiple lines of evidence point to innate immune responses that are elicited by late events of the viral replication cycle ( 13 , 15 , 32 , 33 , 35 , 51 , 87 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells, including the monocyte precursors and their differentiated macrophages and dendritic cells, are among the first targets during HIV-1 infection and transmission [32][33][34]. Myeloid cells are important for viral pathogen sensing and inflammation caused by HIV-1 infection [35,36]. A recent study showed that 2 0 -O-methylation in HIV-1 RNA prevents MDA5-mediated sensing in monocytic cell lines, primary macrophages and dendritic cells, thereby reducing IFN-I induction and innate immune responses to HIV-1 [37].…”
Section: Introductionmentioning
confidence: 99%